2015
DOI: 10.1007/s12098-015-1862-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Learning Disabilities in School Children

Abstract: Learning disability is an important concern in young school aged children. Early identification of such students can help in early institution of intervention and suitable modifications in teaching techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…The study took a sample of 200 teachers and found that there was a statistically significant relationship in overall level of knowledge and teacher gender, education, years of experience, type of school and class being taught. A similar study was conducted by Padhy, Goel, Das, Sarkar, Sharma and Panigrahi (2016) to investigate teacher perceptions about learning disabilities in the public schools of slum areas of Chandigarh, India. A purposive sampling technique was adopted to obtain a sample of 80 teachers from 103 schools there.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study took a sample of 200 teachers and found that there was a statistically significant relationship in overall level of knowledge and teacher gender, education, years of experience, type of school and class being taught. A similar study was conducted by Padhy, Goel, Das, Sarkar, Sharma and Panigrahi (2016) to investigate teacher perceptions about learning disabilities in the public schools of slum areas of Chandigarh, India. A purposive sampling technique was adopted to obtain a sample of 80 teachers from 103 schools there.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8 Its prevalence was reported from 3-15% in school children in India. 9,10 A conclusive diagnosis of SLD cannot be made until the child is about 7-8 years old, as some children are "normal late developers" and they outgrow their learning problems, unlike LD, which is a life-long disorder. 11 However, signs of SLD can be detected in "at risk "children even earlier.…”
Section: Discussionmentioning
confidence: 99%
“…3 On similar lines, a recent study has estimated that learning disability is present in about 3% of thirdand fourth-grade students assessed from a cross-sectional sample. 5 It has been evidenced that usually children with learning disorders have the characteristics, such as attention and concentration difficulties, socialization difficulties, low frustration tolerance, perceptual difficulties, hyperactivity, poor in reading, writing, spellings, and arithmetic. 6 Keeping in mind the abovementioned information, it was thought imperative to explore a pattern of deficits in children suffering from SLDs (mixed type) if any, in order to aid in early detection and early remedial process.…”
Section: Jpmermentioning
confidence: 99%